Comparison of two scores for allocating resources to doctors in deprived areas. Issue 6708 (4th November 1989) - Hutchinson, A.; Foy, C.; Sandhu, B.
Abstract : Current proposals in the general practitioner contract include additional payments to doctors working among deprived populations. The underprivileged area score will be used to identify local authority wards with the greatest levels of deprivation, thus acting as the basis for distributing considerable resources. Two methods of identifying deprived populations–the underprivileged area score and the material deprivation score–were compared to determine whether they result in similar allocation of resources to regions. Financial allocations to regions based on figures derived from the contract differed considerably if the material deprivation score was used instead of the underprivileged area score: Northern and Mersey regions gained over 50% of their allocation whereas East Anglia, Oxford, and South West Thames regions lost more than 30% of theirs. Such differences have considerable implications for doctors working among deprived populations as up to 60m pounds each year might be distributed by these payments.